EDI – A Template-Driven Metadata Editor for Research Data. Issue 1 (25th October 2016) - Pavesi, Fabio; Basoni, Anna; Fugazza, Cristiano; Menegon, Stefano; Oggioni, Alessandro; Pepe, Monica; Tagliolato, Paolo; Carrara, Paola
EDI is a general purpose, template-driven metadata editor for creating XML-based descriptions. Originally aimed at defining rich and standard metadata for geospatial resources, It can be easily customised in order to comply with a broad range of schemata and domains. EDI creates HTML5 [9 ] metadata forms with advanced assisted editing capabilities and compiles them into XML files. The examples included in the distribution implement profiles of the ISO 19139 standard for geographic information [14 ], such as core INSPIRE metadata [10 ], as well as the OGC [8 ] standard for sensor description, SensorML [11 ]. Templates (the blueprints for a specific metadata format) drive form behaviour by element data types and provide advanced features like codelists1 underlying combo boxes or autocompletion functionalities. Virtually, the editing of any metadata format can be supported by creating a specific template. EDI is stored on GitHub athttps://github.com/SP7-Ritmare/EDI-NG_client andhttps://github.com/SP7-Ritmare/EDI-NG_server .